An interval valued intuitionistic fuzzy PROMETHEE approach for hospital service quality evaluation - (:unkn) unknown (World Scientific Publishing Co. Pte Ltd, 2016)
Survival of any company in a competitive industry depends on its ability to provide best service quality to its customers. Healthcare industry is not out of this concern and management of hospitals need to improve their healthcare quality and effectiveness to hold their existing patients and attract new ones. Any service quality improvement effort starts with the evaluation of the current situation, in general, with the consideration of multiple criteria. This study aims to propose a methodology to evaluate the department service quality of a hospital. In the proposed methodology, an interval-valued intuitionistic fuzzy PROMETHEE (IVIF-PROMETHEE) approach is used. © 2016 by World Scientific Publishing Co. Pte. Ltd.